The effect of cellulose phosphate on plasma and urinary magnesium at different levels of parathyroid function in man - Parfitt, A M (Clinical science and molecular medicine, 1976)
1. Previously published data obtained by magnesium infusion in man were found to conform to a Tm/glomerular filtration rate (GFR) model on the assumption of 80% diffusibility of plasma magnesium. The lower limit of Tm,Mg/GFR was 625 mumol/l. 2. Previously published data concerning the effect of cellulose phosphate on magnesium metabolism in normal subjects, patients with latent hypoparathyroidism and patients with primary hyperparathyroidism were found to conform to the same model, with the same limit for Tm,Mg/GFR for all three levels of parathyroid function. 3. The threshold for magnesium excretion is sharper with less 'splay' than for phosphate, but as for phosophate it is close to the normal blood concentration. 4. Because of the geometrical relationship between different methods of presentation of data, at a constant value for Tm,Mg/GFR changes in magnesium load or in GFR automatically produce changes in fractional magnesium clearance. This is the explanation for the increase in fractional magnesium clearance which occurs which with diminishing renal function. 5. Renal conservation of magnesium is a passive consequence of the fall in plasma magnesium. There was no evidence of augmented tubular reabsorption of magnesium in response to magnesium deprivation in any of the three groups of subjects. 6. The tubular reabsorption of magnesium was not altered detectably by a moderate deficiency or excess of parathyroid hormore. Changes in parathyroid hormone secretion are probably not concerned in normal magnesium homeostasis.